Deracemization of Phenyl‐Substituted 2‐Methyl‐1, 2, 3, 4‐Tetrahydroquinolines by a Recombinant Monoamine Oxidase from Pseudomonas monteilii ZMU‐T01. Issue 11 (14th April 2018) - Deng, Guozhong; Wan, Nanwei; Qin, Lei; Cui, Baodong; An, Miao; Han, Wenyong; Chen, Yongzheng
Abstract: A monoamine oxidase (MAO5) from Pseudomonas monteilii ZMU‐T01 was first heterologously expressed in Escherichia coli BL21(DE3) and then used as a biocatalyst for the deracemization of racemic 2‐methyl‐1, 2, 3, 4‐tetrahdroquinoline derivatives to yield the unreacted R enantiomer with up to >99 %  ee . Sequence alignment revealed that MAO5 shared 14.7 % identity toward the well‐studied monoamine oxidase (MAO‐N). Abstract : Situation resolved : A novel monoamine oxidase (MAO5) is heterologously expressed in Escherichia coli BL21(DE3). Deracemization of a variety of 2‐methyl‐1, 2, 3, 4‐tetrahydroquinoline derivatives with different substituents on the phenyl ring by the recombinant monoamine oxidase gives excellent ee values up to >99 % for the unreacted R enantiomer.